P278 Extra-corporeal Membrane Oxygenation And Diffuse Alveolar Haemorrhage – A Single Centre Case Series And Analysis Of The Elso Database. (10th November 2014) - Simpson, TRG; Ling, CY; Glover, G; Barrett, N; Ioannou, N; Lams, B; Langrish, C; Meadows, C; Agarwal, N; D'Cruz, D
Abstract : Background: Diffuse alveolar haemorrhage (DAH) is a potentially fatal complication of the systemic vasculitides and may present directly to the intensivist as a severe acute respiratory distress syndrome (ARDS) with reported mortality of 12- 60%. Whilst a severe respiratory failure (SRF) therapy strategy incorporating extracorporeal membrane oxygenation (ECMO) improves outcomes in ARDS, use of ECMO in DAH is often considered to be relatively contraindicated due to the requirement for systemic anticoagulation. Methods: We present a case series of 4 patients with DAH due to underlying ANCA-associated vasculitides managed by a standardised diagnostic pathway and ARDS treatment algorithm in a single, UK SRF centre, since 2012. We analysed the Extracorporeal Life Support Organisation (ELSO) database and report on the current international experience of DAH and ECMO. Results: The case series is described in Table 1 . Median Lung Injury Score was 3.5. All patients received ECMO (median duration 8 days) and all received immunosuppression. One patient received normal heparin protocol to target APTTr 1.5–2 whilst two patients had 48 h of ECMO with no heparin followed by targeted sub-therapeutic low dose heparin. ICU survival was 100% and six month survival was also 100%. There were no exacerbations of pulmonary haemorrhage, no new events of extra-pulmonary haemorrhage and no clotting complications. ELSO: The ELSO database contains 78 patients (adult, 59; paediatric, 19) with pulmonary vasculitides who received ECMO. 43 had a diagnosis of Granulomatosis and Polyangiitis (GPA), whereas the remaining diagnoses included hypersensitivity angiitis, Goodpasture's syndrome and thrombotic microangiopathy. The median age was 23 yrs (IQR 16–47). The median duration of ECMO was 190hrs (IQR 146–282) and ICU survival was 82%. Twelve patients (15%) were reported to have thrombotic ECMO circuit complications. Conclusion: In this case series, ECMO offers an excellent survival rate in SRF due to ANCA-associated DAH. ELSO registry data supports this, suggesting that ECMO should be considered as supportive therapy in DAH with SRF not responsive to conventional therapy.